Perancangan Sistem Pendukung Keputusan Verivikasi Kelayakan Calon Tenaga Kerja Indonesia (CTKI) dengan Metode Simple Additive Weighting (SAW) - Muhammad Akbar; Dafid Dafid (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2015)
In determining the eligibility of Indonesian Work Force Candidate (CTKI), BPTKI Palembang conducted by selecting their completeness requirements. The existing processes should be improved to minimize mistakes in determining the eligibility of the CTKI. The purpose of this decision support system is to determine the eligibility of CTKI using Simple Additive Weighting method. This research used RUP methodology, PHP language programing and MySQL Database. This Decision Support System produces a list of eligible worker to work abroad in accordance with the ranking so easily in decision.